Algorithms and Human Rights: The Impact of AI Technology on the Protection of Individual Rights - Fadhlurrahman, Muhammad Alfi; Riyanta, Stanislaus; Rustam, Muhammad Reza (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the impact of artificial intelligence (AI) algorithms on the protection of individual rights, with a focus on transparency and accountability. The research aims to analyze how regulations like the GDPR in the European Union influence AI decision-making processes to safeguard human rights. Using a comparative legal analysis method, this research investigates the role of prospective and retrospective transparency in ensuring that AI systems operate ethically and fairly. The results highlight that transparency significantly enhances accountability and user rights, particularly in preventing discrimination and promoting security. The study concludes that collaboration among policymakers, developers, and users is critical to aligning AI technologies with human rights principles, ultimately fostering more equitable and secure outcomes.